Counting and Capturing Crocodilians: CIR1451/UW198, 11/2004 - Cherkiss, Michael S.; Fling, Holly E.; Mazzotti, Frank J.; Rice, Kenneth G. (EDIS, 2005)
With few exceptions, crocodilians must be counted and caught for studies of their ecology. Most methods of finding and catching crocodilians in use today are modifications of methods for harvesting crocodilians (Chabreck 1963; Jones 1966). These methods have been adapted to suit the target species, or local habitat conditions and to minimize risk of injury to the crocodile and the investigator (Webb and Messel 1977; Hutton et al.1987; Walsh 1987; McDaniel and Hord 1990). Any particular situation will likely require innovations on methods used by others. This document is Circular 1451, one of a series of the Wildlife Ecology and Conservation Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published: November, 2004. CIR1451/UW198: Counting and Capturing Crocodilians (ufl.edu)